Laboratory blood analysis in Strigiformes—Part II: plasma biochemistry reference intervals and agreement between the Abaxis Vetscan V2 and the Roche Cobas c501. (22nd January 2015) - Ammersbach, Mélanie; Beaufrère, Hugues; Gionet Rollick, Annick; Tully, Thomas
<x xml:space="preserve">Abstract</x> Background Limited plasma biochemical information is available in Strigiformes. Only one study investigated the agreement between a point‐of‐care with a reference laboratory analyzer for biochemistry variables in birds. Objectives The objective was to report reference intervals (RI) for plasma biochemistry variables in Strigiformes, and to assess agreement between the Abaxis Vetscan V2 and Roche Cobas c501. Methods A prospective study was designed to assess plasma biochemistry RI for concentration of calcium, phosphorus, total protein, albumin, globulin, glucose, bilirubin, uric acid, bile acids, sodium, potassium, and chloride, and activities of AST, GGT, CK, amylase, lipase, LDH, and GLDH. In addition, the agreement between the Vetscan and the Cobas in owl species was assessed. Results A total of 190 individuals were sampled belonging to 12 Strigiformes species including Barn Owls, Barred Owls, Great Horned Owls, Eurasian Eagle Owls, Spectacled Owls, Eastern Screech Owls, Long‐Eared Owls, Short‐Eared Owls, Great Gray Owls, Snowy Owls, Northern Saw‐Whet Owls, and Northern Hawk‐Owls. Order‐, species‐, and method‐specific RI were determined on both analyzers. Although Vetscan data were not equivalent to the Cobas, 4 analytes (glucose, AST, CK, and total protein, with correction for bias) were within acceptable agreement, 3 analytes (uric acid, calcium, and phosphorus) were within close agreement, and the remaining analytes were in strong disagreement. Species‐specific differences were observed notably for the concentration of glucose in Barn Owls and electrolytes in Northern Saw‐Whet Owls. Conclusions Overall, this study suggests that the Vetscan has acceptable clinical performance in Strigiformes for some analytes and highlights discrepancies for several analytes.